POTENSI PENGEMBANGAN USAHA TERNAK KELINCI DI KAMPUNG SEREH DISTRIK SENTANI KABUPATEN JAYAPURA - Hetharia, Lucas Filips; Suparman (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
This study aims to determine the potential for rabbit breeding in Sereh Village, Sentani District, JayapuraRegency. The method used is a survey method with field observation techniques to obtain data throughdirect interviews with farmers with the help of a questionnaire. Samples were taken by census of 3populations of rabbit breeders in Kampung Sereh. The observed variables are natural resource potential,human resource potential, market potential, and government policy support. The results showed thatnatural resources, human resources, and marketing have the potential to develop a rabbit farmingbusiness in Sereh Village, but from the aspect of government policy support it has not provided anopportunity to develop a rabbit farming business in Sereh Village, Sentani District, Jayapura Regency.